PENGKAJIAN PEMANFAATAN DATA TERRA-MODIS UNTUK EKSTRAKSI DATA SUHU PERMUKAAN LAHAN (SPL) BERDASARKAN BEBERAPA ALGORITMA - Prasasti , Indah; Sambodo, Katmoko Ari; Carolita , Ita (Institut Teknologi Sepuluh Nopember, 2007)
Land surface temperature (LST) is one primary parameters energy balance on the surface and also as primary climatology variable that controlling long-wave energy flux through atmosphere. The LST data is needed for drought estimating models which based on calculating of soil moisture lavel and/or evapotranspiration. TERRA satellite that brings sensor MODIS (Moderate Resolution Imaging Spectroradiometer) is an evironmental. Observation satellite that can be used for extracting LST data regionally. The MODIS relatively has width coverage; 2330 Km, and spatial resolution 250 m (1 and 2 channel) with high spectral resolution (36 channels), and temporal resolution that almost similar to the previous generation satellite called NOAA.